Hazard analysis and critical control point (haccp) in a company balanced food for animals (Gestión y Gerencia, 2019)
In food companies quality control is a fundamental aspect since their products are related to the health of consumers. In this research was implemented under the guidelines of Codex Alimentarius and COVENIN Standard 3802: 2002, a system  of Hazard Analysis and Critical Control Point (HACCP) in the company Concentrados Valera Compañía Anónima (CONVACA). The work was carried out in four phases. I: Determine correspondence between functional objectives of the process of elaboration of balanced feed for animals and the strategic ones of CONVACA; II: Diagnosis of the process considering the HACCP guidelines dictated by the Codex Alimentarius and the COVENIN Standard 3802: 2002; III: Formulation of improvement strategies required for the design of the HACCP and IV Implementation of the HACCP  in a pilot zone. The results obtained showed that the process is made up of 25 operations of which 18 presented significant hazards, identifying nine critical control points (CCP). The control limits (LC) were established and corrective, monitoring, verification and registration measures were designed. The pilot test in one of the PCCs with 98% compliance of the system allows to suggest the feasibility of application for the rest of the company's products
Keywords: COVENIN 3802: 2002; Company of Balanced Food for Animals; HACCP